Pengaruh Financial Leverage, Cash Holding, dan ROA Pada Income Smoothing di Bursa Efek Indonesia - Putri, Putu Ayu Diah Widari; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 22 No 3 (2018)DO - 10.24843/EJA.2018.v22.i03.p11, 2018)
The importance of earnings information makes managers often perform dysfunctional behavior in managing the profit received by the company one of them is income smoothing. Managers make income smoothing as a stable and nonfluctuating profit is valued as a good achievement. The purpose of this study is to obtain empirical evidence and discussion about the influence of financial leverage, cash holding, and return on assets in income smoothing on all sectors manufacturing companies listed on the Exchange Indonesia Securities for 2012- 2016. Determination of the number of samples using purposive sampling method, so that samples obtained 54 companies. Hypothesis testing in this research using logistic regression analysis technique. Based on the results of logistic regression analysis obtained that, financial leverage have a positive effect on income smoothing, cash holding has no effect on income smoothing and return on asset has a positive effect on income smoothing. Keywords: Income smoothing, financial leverage, cash holding, return on asse